Partnership Strategy as an Effort to Empower the Economy in Increasing Income and Community Welfare (Case Study on the Business of Sharia Farmers Livestock Cooperative Mitra Subur Bondowoso Regency) - Feby Nurjannah; Misbahul Munir; Abdul Rokhim (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2024)
This study aims to provide an overview and understanding of the implementation of partnership strategies in Islamic economic empowerment to increase community income and welfare. A partnership refers to a cooperative business relationship that serves as a strategic collaboration between two or more parties based on the principles of mutual need, mutual growth, and mutual benefit. Such cooperation inherently involves mentoring and development, as each party possesses its own strengths and weaknesses. These differences complement each other one party compensates for the other's weaknesses through guidance and capacity building, and vice versa. This research employs a descriptive qualitative method, with the researcher acting as the primary instrument. The study was conducted at the Koperasi Ternak Tani Syariah (Sharia Livestock Farmers Cooperative) in Karanganyar Village, Tegal Ampel District, Bondowoso Regency. Data were collected through interviews, documentation, and observation. Data analysis was carried out using data reduction, data display, and conclusion drawing techniques. The data sources used in this study consist of both primary and secondary sources. The results show that the partnership model implemented by KTTS follows the core-plasma pattern, with the institution functioning as the provider of goods and product marketing. The existence of this partnership concept at KTTS has proven to empower its members/partners, enhancing their income and overall welfare. Empowerment is carried out through training that helps members learn how to engage in livestock farming more effectively and efficiently. This, in turn, has a significant impact on increasing the income and well-being of each member.